1958
DOI: 10.1161/01.res.6.6.699
|View full text |Cite
|
Sign up to set email alerts
|

An Electron Microscopic Study of Myocardial Ischemia in the Rat

Abstract: Myocardial iufnrct.s were produced in rats by ligating the anterior descending branch of the left coronaiy artery. After one hour, changes in the ultrastructure of niyofibers in the infarcts were readily demonstrated by ele.tran microscopy. These changes became progressively severe with time, and consisted primarily of swelling of mitochrondria and sarcoplasmic reticulum followed by increased lipid droplets and myolysis. Autolysis of myocardium was also .studied :ind the changes found to be similar to those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1
2

Year Published

1966
1966
1978
1978

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(25 citation statements)
references
References 10 publications
4
18
1
2
Order By: Relevance
“…Reeves The most striking ultrastructural changes on exposure to anoxia in the absence of glucose were the marked morphologic changes in the mitochondria and the dilatation of the longitudinal tubules. It is notable that similar changes in mitochondria and longitudinal tubules have been observed in experimental myocardial ischemia (19)(20)(21)(22)(23). The mitochondria are the cellular sites of aerobic energy generation l)v oxidatixve phosphorylation.…”
Section: Discussionmentioning
confidence: 63%
“…Reeves The most striking ultrastructural changes on exposure to anoxia in the absence of glucose were the marked morphologic changes in the mitochondria and the dilatation of the longitudinal tubules. It is notable that similar changes in mitochondria and longitudinal tubules have been observed in experimental myocardial ischemia (19)(20)(21)(22)(23). The mitochondria are the cellular sites of aerobic energy generation l)v oxidatixve phosphorylation.…”
Section: Discussionmentioning
confidence: 63%
“…In O pie 's [1] study, as well as our own, blood flow through the infarct center was severely diminished, although circula tion was still present due to adjustments in the collateral circulation. Histological studies reveal that regional ischemia results in a gradual, rather than abrupt, deterioration of the infarcted tissue [30,31,33]. It has also been shown that mitochondrial function following regional ische mia increases steadily at varying distances from the infarct center [34], Metabolic alterations appear to be the result of oxygen delivery, as determined by flow rather than blood POa.…”
Section: Regional Blood Flowmentioning
confidence: 99%
“…In contrast to the predominant pattern of muscle cell necrosis in the outer peripheral regions of the infarcts, central regions of the infarcts with severely reduced blood flow contained necrotic muscle cells without contraction bands or calcium deposits. This pattern of myocardial necrosis previously has been shown to be typical of areas rendered maximally ischemic by permanent coronary occlusion (32)(33)(34)(38)(39)(40). Such regions have also been shown to develop a severe impairment to myocardial perfusion within 90-120 min after onset of coronary occlusion (22,28).…”
Section: Tmentioning
confidence: 53%